The Place of Children’s Self-government in the Educational System of Janusz Korczak - Didenko, Alyona (Pedagogical Discourse, 2013)
The article summarized and described teaching experience of J. Korczak in the formation and development of children’s self-government. On the basis of study of works of the leading researchers of the creative work of the outstanding Polish teacher the conceptual principles, structure, content; stages of development of children’s self-government, its social and formational humanistic character are defined. The levels and functions of J.Korczakʼs educational management by development of the children’s self-government are distinguished. Analyzed the educational effectiveness of children’s self-government at the custodial establishments of J.Korczak as a basis for the realization of democratic rights and freedoms of the child, the way of humanization of education, the method of formation of a civil responsibility, with the form of organization of the activity of the younger generation.